THE ROLE OF TEACHER AND STUDENT INTERACTION IN CHILDREN'S LANGUAGE DEVELOPMENT IN EARLY CHILDHOOD EDUCATION (PAUD) 3-5 YEARS - Pardede, Dwi Angeli; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
This study explores the role of teacher and student interaction in fostering language development among children aged 3-5 years in early childhood education (PAUD). Language development is a crucial aspect of a child’s cognitive and social growth during this period. The research employs a qualitative approach, utilizing observations and interviews to analyze the dynamics of teacher-student interactions in selected PAUD institutions. Results indicate that effective teacher-student interaction, characterized by active communication, open-ended questioning, and responsive feedback, significantly enhances children’s vocabulary, sentence structure, and verbal expression. Additionally, a warm and supportive environment encourages children’s confidence in language use. This study underscores the importance of intentional, high-quality interaction between teachers and students in promoting early language development and provides recommendations for best practices in PAUD settings.